1998
DOI: 10.1038/sj.ejcn.1600566
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated oils do not all have the same effect on plasma cholesterol

Abstract: Evidence assembled here indicates that when olive oil forms a major part of dietary fat in controlled human experiments, total and LDL-cholesterols are somewhat higher than when the same amount of fat is one of the modern predominantly monounsaturated oils: low erucic rapeseed or high oleic sun¯ower oil. Oils rich in monounsaturated fatty acids thus do not all have the same effect on plasma cholesterol. This phenomenon is explicable by consideration of the content of other fatty acids and the non-saponi®able f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
1
33
0
2
Order By: Relevance
“…The relation of total fat intake and fatty acid patterns to cardiovascular disease development has been extensively studied (Truswell & Choudhury, 1998;Hegsted & Kritchevsky, 1997;Howell et al, 1997;Hegsted et al, 1993). Current guidelines for the prevention of cardiovascular disease focus speci®cally on saturated fat.…”
Section: Energy and Nutrient Intakesmentioning
confidence: 99%
“…The relation of total fat intake and fatty acid patterns to cardiovascular disease development has been extensively studied (Truswell & Choudhury, 1998;Hegsted & Kritchevsky, 1997;Howell et al, 1997;Hegsted et al, 1993). Current guidelines for the prevention of cardiovascular disease focus speci®cally on saturated fat.…”
Section: Energy and Nutrient Intakesmentioning
confidence: 99%
“…Cardiovascular disease is the number one public health problem in western countries. Recent data showed that diets including 10 to 13% of oleic acid in the total caloric intake could protect from new cardio-vascular events [8], but increasing oleic acid intake to more than 20% of the total caloric intake could limit this beneficial effect by inducing an increase of LDL-C [21,34]. Grundy, in an attempt to clarify the desirable ratio of saturated versus unsaturated (mono and poly) fatty acids, concluded in 1997 to "insufficient data for recommended oleic intake", and proposed for the moment 15-16% as a "reasonable compromise".…”
Section: Discussionmentioning
confidence: 99%
“…Cela peut être évalué par un indice d'agrégation représenté par le rapport plasmatique : acide arachidonique/dérivés n-6 + n-3 (soit 20:4n-6/20:3n-6 + 20:5n-3 + 22:6n-3) qui se trouve être diminué progressivement avec la réduction de l'apport en acide linoléique et/ou par l'augmentation de l'apport en acide oléique de la ration alimentaire. Une revue de différents travaux portant sur la comparaison des huiles mono-insaturées de sources différentes qui vient d'être publiée par Truswell et Choudhury [22] confirme ces résultats et indique clairement qu'à apport quantitatif égal de lipides, les valeurs de LDL-C plasmatiques après des régimes huile d'olive sont « toujours quelque peu plus élevées, par comparaison à d'autres régimes mono-insaturés de type colza ou tournesol oléique ». Comme nous l'avons également montré [16], un apport excessif d'acide oléique peut être responsable d'un déficit dans la représentation plasmatique de l'acide linoléique, et donc devenir moins efficace sur les processus qui conduisent à une meilleure épuration du LDL-C. Outre ce point particulier lié à la qualité des acides gras, des effets hypocholestérolémiants « complémentaires », mais non négligeables s'ils sont cumulés, pourraient être imputés aux qualités des « composés mineurs » des huiles de graine : richesse en phytostérols et pauvreté en squalène, qui font aussi la différence avec l'huile d'olive.…”
Section: Rôle Des Acides Gras Prépondérants Des Huiles De Tournesol Lunclassified